CREB3L1 and CREB3L2 control Golgi remodelling during decidualization of endometrial stromal cells - Pittari, Daniele; Dalla Torre, Marco; Borini, Elena; Hummel, Barbara; Sawarkar, Ritwick; Semino, Claudia; van Anken, Eelco; Panina-Bordignon, Paola; Sitia, Roberto; Anelli, Tiziana (Frontiers in Cell and Developmental Biology, 2022)
Upon progesterone stimulation, Endometrial Stromal Cells (EnSCs) undergo a differentiation program into secretory cells (decidualization) to release in abundance factors crucial for embryo implantation. We previously demonstrated that decidualization requires massive reshaping of the secretory pathway and, in particular, of the Golgi complex. To decipher the underlying mechanisms, we performed a time-course transcriptomic analysis of in vitro decidualizing EnSC. Pathway analysis shows that Gene Ontology terms associated with vesicular trafficking and early secretory pathway compartments are the most represented among those enriched for upregulated genes. Among these, we identified a cluster of co-regulated genes that share CREB3L1 and 2 binding elements in their promoter regions. Indeed, both CREB3L1 and 2 transcription factors (TF) are up-regulated during decidualization. Simultaneous downregulation of CREB3L1 and 2 impairs Golgi enlargement, and causes dramatic changes in decidualizing EnSC, including Golgi fragmentation, collagen accumulation in dilated ER cisternae, and overall decreased protein secretion. Thus, both CREB3L1 and 2 are required for Golgi reshaping and efficient protein secretion, and, as such, for successful decidualization.